THE PHENOMENON OF ONLINE GAMBLING UNDER THE GUISE OF ONLINE GAMES AMONG THE YOUNGER GENERATION - Indra, I Made; Japari, Antony; Novika, Fanny; Septivani, C. Nike; Rosmayanti, Melinia; Karina, Enno; Chalista, Bunga (International Journal of Multidisciplinary Research and Literature, 2025)
The increasing prevalence of online gambling cases among the young generation in Indonesia has a negative impact in that the younger generation is addicted to online gambling games that are easily accessible anywhere 24 hours a day, which only have a Wi-Fi network, through smartphones, and laptops. This study uses a descriptive method with a quantitative approach; the implementation time of this research starts from September 2024 to December 2024. The population in this study is the entire community attracted to the younger generation, namely those aged 17-29 years who use social media, such as Instagram. The research sample is the younger generation willing to become respondents by promoting a questionnaire on Instagram ads for 1 month. The number of respondents in the study was 90 respondents. The results of the study found that the majority of respondents who were exposed to online games under the guise of gambling were young generations aged 17-20 years. This age group is more vulnerable to social and digital influences due to the level of media literacy and self-control that is not fully mature. Involvement in online gambling is influenced by economic factors, such as low income and the assumption that gambling is an easy way to gain financial benefits. Technology, especially stable internet access, and social media is the main means that facilitate this engagement. Influence from friends, social media promotion, and the presence of influencers are the main drivers of respondents' involvement in gambling activities. Many respondents are exposed to online games through their social environment. Online gambling activities under the guise of gaming have had a negative impact, including difficulty controlling spending, increased addiction, and even a desire to go into debt to continue playing. It shows the addictive and destructive nature of gambling. Some respondents believe their skills or experience can increase their chances of winning. This belief encourages them to continue playing even though losses occur more often.